EVALUASI ANGGARAN RENCANA DAN REALISASI ANGGARAN KAS PADA PT PELABUHAN INDONESIA IV CABANG SAMARINDA - Putri, Novi Marinda (EKONOMIA, 2013)
MarindaÂ  Putri, 2012, Evaluation Plan and Budget Actual Budget Cash In PT Pelabuhan Indonesia IV Samarinda Branch under the guidance of Mr. H. Eddy Soegiarto , K and Mrs. Titin RulianaThe purpose of this study to know that there are differences in the cash budget and cash budget realization of PT Pelabuhan Indonesia IV Branch Samarinda and assess the ability of the cash budget . Basic theory of financial management in particular used the cash budget by using the data plan and the realization of the 2001 fiscal year budget and use cash final analysis tools .Based on the analysis and discussion of the conclusions of this study as follows :Results of an analysis of the plan and the realization of the cash budget is happening is known to occur difference in the number of cash balance plans the end of the fourth quarter 2011 were budgeted at Rp420.000.000 , realization of only Rp390.000.000 resulting in a shortfall of 3,000,000.The difference is caused by the presence of actual spending greater exploitation of the plan . PT Pelabuhan IV Branch should Samarinda in estimating end cash balance to be more careful because usually on the fourth quarter in October , November and December is the rainy season so many are reluctant to sail the ship , sail anyway if fixed costs result handlers at the port will be issued by PT Pelabuhan IV Branch Samarinda will swell compared to previous months , should end cash balance plan in 2010 is not too big because it will be the beginning cash balance in 2012 , will consequently affect the overall cash flow. Based on the analysis and discussion of the research hypothesis as a temporary answer of this study was rejected , because the realization Based on the results of the analysis turns cash budget is made smaller than planned .Â